A Comparison of Different Measures for Stabilizing Sand Dunes III the Horqin Sandy-Land, Inner Mongolia, China - Tonghui, Zhang; Halin, Zhao; Fengrui, Li; Shirato, Yasuhito; Ohkuro, Toshiya; Taniyama, Lchiro (Annals of Arid Zone, 2016)
Some measures for preventing moving sand dunes in the Horqin Sandy Land were examined in this study. The results indicated that although all measures significantly increased plant diversity and biomass. but the wheat straw’ checkerboard and transplanting Artemisia ha/odendrom were the most effective. During transition from moving to fixed sand dunes, the successive order of vegetation was Agriophyiium quarrosum, Artemisia halodendrom, Setaria viridis and Artemisia sea/aria